The Utilization of Microsoft Excel for Business Data Analysis: Case Study & Implementation - Nirmala, Endar; Sri Mulyati; Ari Mulyoto (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
Many vocational high school students do not yet possess the proficiency to manage and analyze data optimally. This is due to a lack of understanding of software applications such as Microsoft Excel, which are very useful in business operations. Therefore, this community service activity aims to enhance students' competence in using Excel as a tool for analyzing business data at SMK Letris Indonesia 2. This study used a qualitative method with a case study approach. Data were obtained through interviews with teachers at the school. This research was conducted based on direct practice (hands-on training) regarding the use of Excel, starting from basic functions to advanced features such as pivot tables, conditional formatting, and logic and statistical functions. This research is adjusted to the needs of the business and industrial world (DUDI) so that students can understand the application of Excel in the real world. This activity is in line with the spirit of Merdeka Belajar and the implementation of a project-based curriculum, which emphasizes the importance of mastering practical skills in addition to theoretical understanding. As a result, students can adapt to technological developments and innovate in the business field. In conclusion, training is still needed so that students can improve and develop their abilities